Web 2.0 in Personalised Healthcare: An assessment of mobile Applications for use by women in early stage childcare - Panagiotou, Elena (2013)
In this study, the qualitative assessment of mobile Applications for use by women in early stage childcare is presented. The research aims to the conjunction of Web 2.0 and mobile devices in Personalised Healthcare as a tool of emotion recording, baby tracker, support provision and has an objective the prevention and observation of psychological disorders that affect mothers after giving birth. As a result, a proposed mobile prototype application was designed based on the assessment's data, used as "Pocket therapist" that monitors the emotions of the mothers. Hence, the study classifies how web 2.0 can develop a solution for the effective design of a mobile application regarding to the research problem arises. As a result, web 2.0 is identified as a tool of self-management and Postpartum Depression diagnosis and observation. Since the study identifies the computer science view of the research problem it has views to the depth analysis of problem using psychological and medical approach as well.